Private Equity and Venture Capital’s Role in Catalyzing Sustainable Investment : Input Paper for the G-20 Sustainable Finance Study Group - Ahmad, Reyaz A. (International Finance Corporation, Washington, DC, 2018)
A defining characteristic of the private equity and venture capital (PE and VC) investment style is the injection of expertise (including technical knowledge, industry relationships, management skills, and so on) in conjunction with risk capital into enterprises to help them grow, improve their performance, and achieve strong financial returns. Harnessing this investment style in the pursuit of sustainable growth and investment is central to achieving the innovation needed for sustainable development. PE funds increasingly align with value creation linked to social and environmental considerations. PE firms are recognizing the material value brought by sustainable businesses and social enterprises, which has resulted in a greater availability of sustainable PE capital that follows, to varying degrees, one or more of the disparate standards being developed or already in the market. This paper focuses on key aspects of sustainable PE and VC market development and deployment. It discusses: (1) why sustainable PE and VC is a useful tool to catalyze other types of capital to achieve sustainability objectives, (2) best practices and lessons learned from the experiences of knowledge partners, (3) the main barriers to further developing the sustainable PE and VC market, and (4) options for countries to voluntarily consider or adopt to overcome these barriers.